Formation of a Strategic Management Model for Enterprises on the Basis of a Fractal Approach - Svetlana DROBYAZKO; Yuliia MELNIKOVA (Communications of International Proceedings, 2020)
Based on fractal theory and the provisions on fractal structuring concerning socio-economic systems, the essence of the restaurant business has been defined as a complex, unstable, self-similar, fractal production and service system that seeks for self-development; a conceptual model of the system of the restaurant industry functional fractal determinants (range, technology, management, marketing, development dynamics and hierarchy) and a fractal model of the restaurant industry by organizational approach have been developed (person, position, unit, enterprise, merger of enterprises (network, cluster) restaurant services market). On the basis of the basic evolutionary principles system (necessity, sufficiency, controllability, self-organization, variability, structural-functional systematic, unity and infinity), a hierarchy of enterprises fractal determinants in the restaurant industry was formed.
Keywords: Fractal Theory; Strategic Management; Hierarchy; Determinants; Development.